Physicochemical assays for the evaluation of the quality of a Costa Rican brand of valerian herbal tea - Mora Román, Juan José (2018)
The ingestion of tea in the population has become a daily practice for the administration of substances with pharmacological properties, like valerian. The objectives were to evaluate some aspects of the physicochemical quality of valerian tisanes of a brand marketed in Costa Rica through various tests established in the Central American Technical Regulation (RTCA) 11.03.56.09 and to identify if these aspects were maintained for three batches of the same product. The following assays were carried out using the procedures found in various official documents in Costa Rica (RTCA 11.04.41:06, United States Pharmacopeia, British Pharmacopoeia, World Health Organization) for three batches: organoleptic tests, labeling requirements, identification, foreign material, minimum fill, loss on drying and total ash. The three batches were compliant to the specifications given by the identification, foreign material, minimum fill (although t values were much higher than the labeling) and loss on drying assays, while they were found to be non-compliant or batch 1 and the one of total ash was non-compliant for batch 3. Therefore, there was variability in the results between the different batches for organoleptic and total ash assays. This shows that there is no strict control over the origin and the process of the raw material used for the preparation of the tisanes, as well as the final product manufacturing process (filling process control) to be commercialized in the national market, causing variations in it.